Design and Implementation of CNC Milling Bot for Milled Circuit Board Fabrication - Kannan Megalingam, Rajesh; Rajesh Raagul Vadivel, Shree; S, Sreekumar; Sekhar, Swathi; R Nair, Thejus; RR, Midhun (International Journal of Engineering and Technology, 2018)
This research paper presents an alternative way to fabricate a Milled Circuit Board (MCB) with the help of a Computer Numerical Controlled (CNC) milling robot. Printed Circuit Boards (PCB) are one of the most widely used control modules in electrical and electronic industries. In this research paper we propose a computer controlled milling machine which can be used for quick fabrication of double layered PCBs called MCB where a user wants to test the circuit without the need to wait for the conventional PCB fabrication. The end effector of the CNC milling machine has the provision to move in 3 axes-x, y and z in accordance with the input received from the controller. DipTrace, an EDA/CAD software is used for creating the schematic diagram for the milled circuit boards. The design to be engraved on the copper clad board is uploaded to a software called CopperCam, where it can be converted to G-code files after making the necessary modifications. These G-code files are then uploaded to the CNC machine using the software Universal G-code Sender, thus enabling the microcontroller to direct the rotation of motors and coordinate the movements of the end effector so as to engrave the board design on to a copper clad.Â Â